Literature Review: Problems and Solutions for Tardiness among Administrative and Financial Staff at the Regional Secretariat of Yogyakarta City - Rahardianto, Arko; Utami Puterisari, Dwi (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
Employee tardiness, particularly in the administration and finance departments, poses a significant challenge that can hinder organizational efficiency. In the Yogyakarta City Regional Secretariat, the tardiness rate reached 24.38% over the past two years, highlighting the urgent need for intervention. Contributing factors include poor time management skills, organizational culture, and environmental challenges such as traffic congestion. The impacts of tardiness not only reduce productivity but also affect employee morale and public perception of government institutions. Strategies to mitigate tardiness include enhancing time management training, fostering a culture of accountability, and implementing flexible work arrangements. Successful case studies from other organizations demonstrate the effectiveness of digital attendance systems and flexible work setups in improving punctuality. By adopting a comprehensive approach and involving employees in finding solutions, the Yogyakarta City Regional Secretariat can enhance attendance and overall organizational performance. Addressing tardiness requires a collaborative commitment from both management and employees to foster a culture of punctuality and accountability, ultimately leading to better public service delivery.